2021
DOI: 10.1111/nph.17780
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural land‐use favours Mucoromycotinian, but not Glomeromycotinian, arbuscular mycorrhizal fungi across ten biomes

Abstract: Globally, agricultural land-use negatively affects soil biota that contribute to ecosystem functions such as nutrient cycling, yet arbuscular mycorrhizal fungi (AMF) are promoted as essential components of agroecosystems. Arbuscular mycorrhizal fungi include Glomeromycotinian AMF (G-AMF) and the arbuscule-producing fine root endophytes, recently reclassified into the Endogonales order within Mucoromycotina. The correct classification of Mucoromycotinian AMF (M-AMF) and the availability of new molecular tools c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 73 publications
1
28
0
Order By: Relevance
“…Glomeromycotina sequences were detected in the root compartment of oil palm in all plantations, suggesting the presence of the arbuscular symbiosis within palm roots. Currently, M-AMF forming the fine root endophyte arbuscular morphology has been linked to a small clade within the Endogolales, centered on OTU0 and OTU4 from Orchard et al (2017), the latter showing 100% sequence match to the only described species of M-AMF fine root endophyte, Planticonsortium tenue (Albornoz et al, 2021). Albornoz et al (2020a,b) found FRE colonization in 44 of 58 Australian pastures sampled, and 92% of the associated Mucoromycotinian sequences clustered within this clade, with 74% of sequences belonging to three OTUs which were distinct from both OTU0 and 4.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Glomeromycotina sequences were detected in the root compartment of oil palm in all plantations, suggesting the presence of the arbuscular symbiosis within palm roots. Currently, M-AMF forming the fine root endophyte arbuscular morphology has been linked to a small clade within the Endogolales, centered on OTU0 and OTU4 from Orchard et al (2017), the latter showing 100% sequence match to the only described species of M-AMF fine root endophyte, Planticonsortium tenue (Albornoz et al, 2021). Albornoz et al (2020a,b) found FRE colonization in 44 of 58 Australian pastures sampled, and 92% of the associated Mucoromycotinian sequences clustered within this clade, with 74% of sequences belonging to three OTUs which were distinct from both OTU0 and 4.…”
Section: Discussionmentioning
confidence: 99%
“…Overall the evidence suggests that M-AMF were not present on oil palm roots. In a study of Australian biomes, Albornoz et al (2021) found that across 10 Australian biomes putative M-AMF were favored by agricultural land use, were rare or absent in native ecosystems, but were not found in tropical biomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MFRE have a wide distribution across plant lineages and ecosystem types, from lycophytes in European heathlands (Kowal et al, 2020) to legumes in Australian pastures (Albornoz et al, 2021), with a potentially prominent role in host plant N nutrition (Field et al, 2019). Because of this, as well as experimental possibilities opened up by isolation and axenic culture experiments, future research into MFRE promises exciting new insights into plant N acquisition both at individual, community, and potentially even agricultural (Albornoz et al, 2022) levels. How this fits mechanistically and ecologically with other forms of mycorrhizas, involving both saprotrophic and obligately biotrophic fungi, is a key area for further study that can be facilitated by new molecular and bioinformatic tools.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…In that study, pH had the strongest effect on the diversity of fungi. This finding is also consistent with Albornoz et al (2022) which found M-AMF preference for acidic soils across a wide sampling of agricultural sites in Australia. Still, more studies have focused on G-AMF ecological requirements, without differentiating M-AMF.…”
Section: Environmental Factors Affect M-amf Colonization Community Ri...mentioning
confidence: 99%